FRIENDSHIP AND CULTURAL RELATIONS BETWEEN UZBEKISTAN AND GERMANY (Academia Science Repository, 2023)
The activities of the German-Uzbekistan society have been supported by the Embassy of the Republic of Uzbekistan in Germany and the Consulate General of the Republic of Uzbekistan since its establishment; the embassy and consulate general follow the work of the society with great interest and in some cases contribute financially to the success of the events. Live communication with the Embassy and Consulate General has a positive effect on the development of the community program. The German-Uzbekistan Society wants to expand the mutual knowledge about Germany and Uzbekistan and does this by organizing events on the topics of culture, politics, business and science.